2
$\begingroup$

I would like to know how to get the solution of the following differential equation:

$$\frac{d^2x}{dt^2}(t)=e^{-x(t)}$$

A differential equation of similar form appears in a paper (Rapp & Kassal 1968) that I'm studying. The authors show us its solution (it involves an hyperbolic secant function), but don't tell us how did they get it. So, at least I know that this differential equation has an analytical solution.

$\endgroup$
10
$\begingroup$

We have $$\ddot x=e^{-x}\\\dot x\ddot x=\dot x e^{-x}$$Integrate both sides with respect to $t$.

$$\frac12 \dot x^2=C_1-e^{-x}\\\int\frac{\mathrm dx}{\sqrt{2(C_1-e^{-x})}}=\int\mathrm dt$$ This can then be integrated using the substitution $u=e^{-x}$.

Edit: On second thoughts, the substitution $u=\sqrt{C_1-e^{-x}}$ works pretty well, giving $$\frac1{\sqrt2}\int\frac{\mathrm du}{C_1-u^2}=\frac1{\sqrt{2C_1}}\tanh^{-1}\left(\frac{u}{\sqrt{C_1}}\right)=\frac1{\sqrt{2C_1}}\tanh^{-1}\left({\sqrt{1-\frac{1}{C_1e^x}}}\right)$$

$\endgroup$
  • 2
    $\begingroup$ You can also use $u=e^{x/2}$. Lots of possibilities! $\endgroup$ – Dylan Jan 7 at 16:47
  • $\begingroup$ Thank you very much for the help! $\endgroup$ – Élio Pereira Jan 7 at 16:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.